2011
DOI: 10.1177/0143624410389580
|View full text |Cite
|
Sign up to set email alerts
|

Micro wind turbine performance under real weather conditions in urban environment

Abstract: The aim of this article is to evaluate the performance of micro wind turbines in a built-up environment. For this purpose, five independent micro wind turbine systems, consisting of two distinctly different models, were tested and evaluated under real life conditions over a period of 12 months. This article provides an overview of the experimental set-up used to test the two different micro wind turbines and then goes on to present the basic background theory for horizontal axis micro wind turbines and the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…For a typical wind turbine, Muljadi et al suggest a C p -λ of around 42% [20]. When this is considered in conjunction with typical generator efficiencies of around 90% [21] and converter losses of 5% [22], wind turbines can have overall efficiencies in the order of 30% [23].…”
Section: Wind Energy Conversionmentioning
confidence: 99%
“…For a typical wind turbine, Muljadi et al suggest a C p -λ of around 42% [20]. When this is considered in conjunction with typical generator efficiencies of around 90% [21] and converter losses of 5% [22], wind turbines can have overall efficiencies in the order of 30% [23].…”
Section: Wind Energy Conversionmentioning
confidence: 99%
“…From the available literature considering urban wind energy, it is obvious that there are two established metrics within the industry that characterise the urban wind regime and its limited energy exploitation; a lower annual mean wind speed caused by the roughness of the environment, and a more turbulent flow created by the associated complex topography [6,7]. Many studies [2][3][4][5][6][7][8][9][10] have illustrated that the urban environment can significantly decrease productivity of a wind turbine installation in comparison to areas boasting more laminar wind profiles, with some studies demonstrating turbine capacity factors as low as 1% for urban installations, in comparison to typical factors of 30-40% for turbines in isolated areas [4]. It has even been shown that due to the high roughness of the urban environment and subsequent lower wind speeds compared to a typical rural climate, micro-wind turbines can actually become net consumers of energy [5].…”
Section: Urban Wind Energy and Atmospheric Turbulencementioning
confidence: 99%
“…Micro/small-wind turbines are being installed predominantly in rural environments. There are studies where the performance of these technologies has been analysed in more urban environments [2][3][4][5]; however, there is still a lot of confusion relating to the performance and generating capability of these technologies in such areas due to variations in surface topography, temperature influences and the dynamic nature of such environments leading to the development of turbulent air masses. In the context of this paper, atmospheric turbulence can be considered as the small-scale, irregular air motions characterised by winds that randomly vary in both speed and direction, as that often indicated by lulls and gusts in the wind.…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, a research work related to the performance of wind micro-turbine, in an urban environment, under real climatic conditions was also published [3]. The method used to estimate the wind potential was to record, using a Davis Vantage Pro2 plus weather station, data on wind speed, wind direction, atmospheric pressure, and humidity.…”
Section: Introductionmentioning
confidence: 99%